An evaluation of secondary school mathematics textbooks in light of sustainable education in Zimbabwe - Sunzuma, Gladys; Luneta, Kakoma (LUMAT: International Journal on Math, Science and Technology Education, 2023)
Mathematics plays a major role in overcoming future challenges, and mathematical skills as well as problem-solving skills might help provide apt solutions to existing and upcoming economic, social and environmental challenges. Textbooks play a major role in mathematics lessons, and they influence how concepts are taught and learners’ understanding of the concepts. The article analysed secondary school mathematics textbooks to find out how they were aligned with sustainable development goals. Content analysis was used to analyse four textbooks that are mainly used in the teaching and learning of mathematics at the secondary school level which are forms one to four in Zimbabwe. The aim was to present how education for sustainable development related content is addressed in the textbooks. According to the findings of the study, the three dimensions (economic, social and environment) of sustainable development goals were reflected in the four mathematics textbooks. Most of the sub-contents in the three dimensions were covered in the textbooks except for climate change, human rights, peace and security, sustainable consumption and narrowing the gap between the rich and the poor.